The Relationship Between Knowledge Management And Malaysian Digital Banking Reputation - Ali Husseini, Saleh; Soo-Fen, Fam; Ali Al-shami, Samer (Opción, 2019)
Purpose - Digital banking service is considered as the new revolution of banks in nowadays. The skills of digital banking service still green mature in Ma- laysia yet. Hence, there need some tools to pretend any issues happened. This purpose of this study is The relationship between Knowledge Management and Malaysian Digital Banking Reputation. Design/methodology/approach - Cross-sectional design was used in the study, and developed questionnaires were administered to 100 employees the executive management team level and above in banks dyads working in Malaysia. IBM-SPSS software is used to analyse the collected data from respondents. PLS-SEM is used to examine the relationship between latent variables to test the proposed relationships. Find- ings - The findings indicated that Knowledge Management Processes helped in Enhancing Malaysian Digital Banking Reputation, which combat financial crimes through strengthening its anti-money laundering and terror financing capabilities, so as to maintain their global competitive edge in this domain. Research limitation/recommendation – the majority of respondents are from executive management and fewer from top management. Usually, top man- agement are the one who plan and control the whole company worked. There- fore, there might be some different to the perspective of bank employees from executive and top management. This survey also based on the perception of employees which could exist some bias on their answer. Practical implica- tions – This Findings of the research can be utilized by banks to Enhance digital banking reputation, which has been identified as a key to growth and development. Taking a knowledge-based view (KBV) of the bank provides a deeper understanding of why some banks are more successful at deploying knowledge management than others. Originality/value – this kind of study is considered as one of the investi- gating study in the regards of the digital banking. Malaysia still in proof digital banking. Hence, reputation can influence decision and confidence of customer